The Dark Side of Cultural Heritage Protection (Faculty of Law, Universitas Negeri Semarang, 2022)
ABSTRACTThis article introduces the concept of the dark side of cultural heritage protection. The existence of strict legal protection with burdensome sanctions is expected to provide a sense of security for a country to protect its cultural heritage from threats from other countries or communities. However, it is an unavoidable fact that the efforts of a country that wants to protect its culture lead to conflict and the threat of war between countries. This article shows how many and most of the excessive efforts of an organization to protect cultural heritage from the dangers of war and conflict contribute and have the potential to make cultural heritage vulnerable or even lead to its destruction. The more we talk about cultural heritage and the values it contains and the importance of protecting it, the more attractive it becomes for some groups, organizations, and even countries to target it because it has extraordinary cultural values. For some, efforts to protect and save cultural heritage have been considered as part of the war against terrorism. They destroy a cultural heritage on purpose to kill profitable tourism. This causes the owner community to lose their rights and even leads to revenge until a war occurs between communities, organizations, or countries. Art and culture have moved to the forefront of war, both as additional damage and direct targets for belligerents who use cultural destruction as a means to encourage more violence, hatred, and revenge. This article argues that states, international organizations, and cultural heritage communities need to recognize these negative side effects and make sure to consider them in future action. Keywords: Conflict; Cultural Heritage; The Dark Side; Legal Protection